Roles of the Peripheral and Autonomic Nervous Systems in Learning: A Systematic Review Bridging Neuroeducation and Islamic Education - Yusuf Efendi; Aljamedi Aljamedi; Syafril Syafril (Ruhama : Islamic Education Journal, 2026)
This study aims to analyze the functions of the peripheral nervous system and autonomic nervous system as the neurobiological foundation of learning and to examine their relevance in strengthening the theoretical framework of neuroscience-based Islamic education. The study employed a Systematic Literature Review method involving 30 scholarly articles covering health neuroscience, autonomic nervous system research, neuroeducation, neuromyths, and neuroscience-based Islamic education. Data were analyzed using thematic analysis and narrative synthesis to identify relationships among nervous system functions, learning processes, and Islamic educational concepts. The findings indicate that the autonomic nervous system plays a significant role in regulating attention, memory, emotions, motivation, decision-making, and learning behaviors. Neuroeducation literature explains that the balance between sympathetic and parasympathetic nervous system activities contributes to cognitive, affective, and behavioral processes that support effective learning. Furthermore, the synthesis reveals that Islamic educational concepts such as intellect ‘aql, dhikr, tafakkur, muhasabah, and character development are closely related to neurological mechanisms described in contemporary neuroscience. This study concludes that the autonomic nervous system serves as a neurobiological foundation linking neuroscience, neuroeducation, and Islamic education within a holistic and integrative learning framework.Keyword: Autonomic Nervous System, Peripheral Nervous System, Neuroeducation, Learning, Islamic Education, Neuroscience.